Manajemen Dakwah Muslim Footballers Bogor dalam Aktivitas Keagamaan para Pesepak Bola - Muhammad Raihan; Komarudin Shaleh; Nia Kurniati (Bandung Conference Series: Islamic Broadcast Communication, 2024)
Abstract. Muslim Footballers Bogor is one of the soccer communities as a forum for Muslim Footballers Bogor is one of the soccer communities as a forum for preaching, by carrying out religious activities such as covering aurat in playing soccer, sharing with fellow humans. This study aims to determine the da'wah strategy of Muslim Footballers Bogor. This research uses management theory, namely Planning, Organizing, Actuating, and Controlling. Qualitative methods are used to examine how planning, organizing, implementing and controlling in the sustainability of religious activities of Muslim Footballers Bogor. The research findings highlight planning; initiating to cover the aurat, preaching through the media and Fastabiqul Khairat. Organizing; this is done by working together with each other. Implementation; through the method of da'wah bil hal (covering the aurat, caring about fellow humans), bil Qalam (posting pieces of Al-Qur'an and hadith verses on social media), Controlling; able to provide significant changes for members of the Bogor Muslim Footballers. Thus, Muslim Footballers Bogor provides a new color in the world of football in terms of Islamic religion. Abstrak. Muslim Footballers Bogor merupakan salah satu komunitas sepak bola sebagai wadah dalam berdakwah, dengan melakukan aktivitas keagamaan seperti menutup aurat dalam bermain sepak bola, berbagi ke sesama manusia. Penelitian ini bertujuan untuk mengetahui manajemen dakwah Muslim Footballers Bogor. Penelitian ini menggunakan teori manajemen, yaitu Planning, Organizing, Actuating, dan Controlling. Metode kualitatif digunakan untuk mengkaji bagaimana perencanaan, pengorganisasian, pengimplementasian dan pengendalian dalam keberlangsungan aktivitas keagamaan Muslim Footballers Bogor. Temuan penelitian menyoroti perencanaan; menggagas untuk tutup aurat, dakwah melalui media dan Fastabiqul Khairat. Pengorganiasian; ini dilakukan dengan bekerja sama satu sama lain. Pengimplementasian; melalui metode dakwah bil hal (tutup aurat, peduli dengan sesama manusia), bil Qalam (postingan potongan ayat al-qur’an dan hadits di media sosial), Pengendalian; mampu memberikan perubahan yang signifikan bagi anggota Muslim Footballers Bogor. Dengan demikian, muslim Footballers Bogor memberikan warna baru dalam dunia sepak bola dari segi keagamaan islam.